A Vietnamese-American cross-cultural study of verbal and nonverbal behaviors in marriage proposal . M.A. Thesis Linguistics: 60 22 02 - Nguyễn, Thị Thái (University of Languages and International Studies, 2017)
This paper is carried out at endeavor of investigating verbal and nonverbal behavior used in marriage proposal by the Vietnamese and American. From that, major similarities and differences between the two languages in this regard are revealed. On the basis of quantitative and qualitative methods, 70 clips are selected to collect data from Vietnamese people and American ones who are currently living in big cities. The result reveals that Indirectness + Directness is the most common strategy used by the Vietnames e and the American in terms of verbal behavior. Medium rate, pitch, volume, short pause and direct eye contact, formal postures, hand holding, hugging, kissing are mostly used by both Vietnamese and American people in terms of nonverbal behavior. Besides, the study goes deeply in the differences between the two cultures